Students Responses in Learning Pronunciation through English Songs at Sixth Grade Student at SD Al-Araf: Penelitian - Nurul Della Salwa; Meristika Moetia (PT PUSTAKA CENDEKIA GROUP, 2026)
English pronunciation remains one of the most challenging skills for young EFL learners, and engaging, low-anxiety media such as songs are often recommended to support its development at the elementary level. This study aims to examine sixth-grade students' responses to learning pronunciation through English songs at SD Al-Araf. A quantitative descriptive research design was employed, involving 20 sixth-grade students selected through purposive sampling; data were collected using a 16-item Likert-scale questionnaire covering four aspects, namely interest, motivation, confidence, and perceived improvement, and analyzed descriptively using means, standard deviations, and percentages. The results showed that students' total scores (sum of 16 Likert-scale items) ranged from 56 to 77, out of a theoretically possible range of 16–80, with a mean total score of 70.15 (SD = 5.46); 75% of respondents were classified into the